Analisis Pendekatan Berbasis Tipological Hippocrates-Galenus dalam Mereduksi Stres Kerja Internet Generation - I Putu Dharmawan Pradhana; Putu Riski Acarya Sadnya Agung; Anak Agung Istri Agung Maheswari; Anak Agung Ngurah Oka Suryadinatha Gorda (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to determine the Hippocrates-Galenus Typology approach in reducing stress and developing the performance of Generation Z in Gianyar. The objects to be studied are Generation Z who are already working, carried out at Mori Mori Food Tampaksiring and Mori Mori Food Sukawati. This research is a qualitative research that uses qualitative data in the form of information about performance and stress at work by conducting interviews with generation Z. The research informants used a purposive sampling technique. Data analysis techniques use Nvivo 12 Plus software. The conclusion of this study is that the stress experienced by generation Z workers is caused by several factors such as work pressure, mental readiness in facing the world of work, and adaptation to a new environment. The company applies an approach based on the Hippocrates-Galenus typology to its employees who experience stress, such as employees who have a melancholic personality. The approach tends to be subtle and gentle so that people with a melancholic personality can receive input and suggestions from superiors without feeling pressured.